Importance of the 3c trituration in the manufacture of homœopathic medicines - Dellmour, F. (British Homeopathic Journal, 1994)
Based on the original trituration of gold made in 1818, Hahnemann introduced trituration to the 3c as a general method for use in homœopathic pharmacy from 1835 onwards, thus distancing himself from the use of solutions and mother tinctures. He found that 3c triturated medicines were more effective, with constituents retained to a much higher degree and improved storage qualities.
Keywords: Manufacture of homœopathic medicines; 3c trituration; Trituration of fresh plants; Mother tincture; Trituration